RANCANG BANGUN ANTENA YAGI DENGAN MENGGUNAKAN MMANA-GAL UNTUK PENGUAT SINYAL GSM FREKUENSI 1800 MHz - Prasetyo, Aji Diode; Purnawan, Peby Wahyu (MAESTRO, 2019)
Antennas are devices that play a very important role in the cordless communication system. In general the antenna function is as a wave modifier that is passed on the transmission line into a free space wave and vice versa. In this thesis, the research conducted is the design of Yagi antenna as a signal amplifier 4G LTE modem based on the frequency of 1800 MHz. Design process aided by MMANA-GAL software. This research aims to determine the feasibility parameters of an antenna in strengthening the modem signal. Includes parameters of QOS (Quality of Service) Latency, Jitter, and Througput. The research aims to determine the performance of Huawei E3276 4G LTE modem before using Yagi antenna and after using Yagi antenna. The tests were conducted at one location and differed in height by 10 meters, 15 meters, and 20 meters at 10 °, 15°, and 20 ° angles set the degree clockwise. The results of the test on the antenna Yagi obtained the results before and after using Yagi antenna. From the results before using Yagi antenna Latency 31 MS, Jitter 122 MS, Download 0.8 Mbps, and Upload 3.7 Mbps. Meanwhile, after using the antenna Yagi get different results-the difference in each height and angle of the degree. The results in each test at a 15 ° angle are said to be well-compared with angles of 10 ° and 20 °. Keywords: Yagi antenna, LTE, QOS (Quality of Service), Latency, Jitter, Througput.